FLOOD CONTROL ALTERNATIVE OF CIDURIAN RIVER REGENCY OF SERANG, PROVINCE OF BANTEN - GHALIB AUSTIN (NIM : 15813038), AZMI
Flood is a natural phenomenon that has destructive power due to high rainfall and insufficient capacity of water bodies (river or drainage channels) to accommodate and drain water. Conditions that occur in Cidurian river flow, characterized by drought during dry season and flood in the rain season. This is exacerbated by significant changes in land cover from year 2009, namely the decline in the function of plantation forests, the high increase of shrubs, and the development of settlements that make the run off become larger so as to contribute a heavy flood. Then there was the degradation of hydraulic structures in the river buildings caused by sand mining, and local scouring which gives the effect of high discharge. The paper aims to plan an alternative flood control for the Cidurian river with retaining wall using HEC RAS 5.0 software modeling assistance. The design of the flood control plan is based on geological data, rainfall data, and crosssection of the Cidurian River. This plan uses flood discharge during the 25th period of 1,473.33 m3/sec and 1 meter as the guard height, so there are 2 alternatives to overcome the flood, which for the first alternative is made to design the retaining wall only with the height vary from 15 - 17 meters. As for the second alternative is made to design the retaining wall with a height of 5 meters and also embankment with varying heights between 1 - 5 meters are adjusted depending on the flood waters that occurred at the cross section.